Implementasi Metode Pembelajaran Sistem Rotasi untuk Meningkatkan Karakter dan Ketuntasan Belajar: (Pembelajaran Hybrid, dan Tatap Muka di Sekolah) - Erni; Handoko; Deviyanti Pangestu; Ismu Sukamto (Arden Jaya Publisher, 2022)
This study aims to determine the mastery of student learning, student understanding, and the formation of good character in learning during the unfinished covid-19 pandemic. The research was conducted at SDIT Asmaul Husna, on Jl. Lapangan Tritura, Kedondong District, Pesawaran Regency, Lampung Province for 1-2 months. The research method used is descriptive qualitative. Descriptive research is research whose main purpose is to present complete data about the social picture for exploration, clarification, or discovery of a social phenomenon. Research results 1). The formation of the character of students during the pandemic will be maximized by learning the rotation system when compared to full online learning. 2). Completeness of learning is maximized because students and educators can discuss directly. 3). Improve students' understanding in mastering learning materials. 4). The lack of parental concerns about students affected by the Covid-19 disease.